Identifikasi Kepuasan Siswa Terhadap Pembelajaran Fisika Dengan Model Pembelajaran Daring Diera Pandemi Covid-19 - Aprilianti, Indah Putri; Rokhmat, Joni (Indonesian Journal of STEM Education, 2021)
Online learning can take place through synchronous or asynchronous formats. Physics is a science or natural science that studies matter and its motion and behavior in space and time, along with related concepts such as energy in force. The general objective is to determine student satisfaction with physics learning using the online learning model during the Covid-19 pandemic. There were 100 respondents from class XII of SMA Negeri 1 Narmada. The type of research used was qualitative research with a survey method. Qualitative research is naturalistic research without intervention from the researcher, producing descriptive data. A survey is research conducted to obtain specific information or characteristics from a population using questions. These questions were compiled in a questionnaire using the Google Forms application. The results of this study indicate that online learning for physics lessons has not achieved student learning satisfaction. The author found that 43.0% felt neutral or satisfied, 30.0% felt dissatisfied with online learning, 10.0% felt very dissatisfied, and 17.0% felt satisfied with online learning.